Hydrogeochemical study at a reforestation area from Itu city, São Paulo State, Brazil - Lee, Isabella G. [UNESP]; Bonotto, Daniel M. [UNESP] (Springer Nature, 2025)
The Itu city at São Paulo State, Brazil, has a significant dependence on surface waters availability, facing difficulties for their supply over the last years due to the accentuated population growth in the region. Thus, the demand for groundwater use raised there what is specifically true for the Forest Experiment Center, managed by the NGO SOS Atlantic Forest and located within the Water Resources Management Unit (UGRHI) 10—Sorocaba and Médio Tietê. Nowadays, there is incipient hydrogeochemical knowledge of those groundwater resources and, in addition to the area having suffered a severe water crisis, the water quality of the surface waters of this region is poor to regular, according to some reports, as a consequence of the activities developed there. Therefore, this study focused that site, aiming to get a better understanding of the hydrogeochemical processes occuring there and their implications for water quality, once the urban growth usually results in changes in the hydrologic cycle with possible pollutants releases. Physicochemical parameters and inorganic compounds of the waters were analyzed in order to identify possible anomalous concentrations of contaminants, especially those related to agricultural activities such as nitrogen and phosphate fertilizers, since the area was used for agriculture before reforestation. The radionuclides radon (222Rn) and radium (226Ra) were also analyzed as the study area is located near the Botuxim deposit, a low-level nuclear waste disposal site that may be a possible source of contamination. Additional motivation for characterizing radon in the study area consisted on its use as a natural tracer to understand hydrogeological processes, as well as by its great risk to human health. This work has taken into account the results obtained during one monitoring campaign held for the following sampling: (1) nine tubular wells drilled at Tubarão Aquifer System; (2) one surface water from a dam (reservoir) built in the area; (3) rainwater. Results show that groundwater samples are generally alkaline, with pH values between 6.24 and 8.51, and total dissolved solids (TDS) ranging from 67.22 to 119.17 mg/L. Those waters are slightly oxidizing, with Eh values between + 188 to + 284 mV. Most of groundwaters are sodium-bicarbonate dominated, except two samples that are mixed in terms of dissolved anions. The dam (reservoir) water and rainwater are mixed in terms of dissolved cations, but dominated by chloride (dam water) or bicarbonate (rainwater). The phosphate levels exceeded the Brazilian standards for human consumption in some samples, which is probably associated with the ancient agricultural activities of the region, because the aquifer’s rocks are not naturally enriched in PO43−. 222Rn activity concentration reached a maximum value of 32.8 Bq/L, below of the previous WHO's recommended limit of 100 Bq/L, while the highest 226Ra activity concentration was 0.12 Bq/L, almost ten times lesser than the 1 Bq/L limit set by the WHO for drinking water. The findings of this investigation show that the radon and radium levels in the waters are within safe limits, indicating that probably there is no influence of the Botuxim deposit on the study area. Thus, the results of such hydrogeochemical survey are essential to ensure adequate planning and management of that region's water resources, helping to understand possible processes affecting the water quality in the area.
Keywords: Groundwater; Hydrochemistry; Itu city at São Paulo State in Brazil; Radon and radium; Tubarão Aquifer System